The photophysical properties of triisopropylsilyl-ethynylpentacene: a molecule with an unusually large singlet-triplet energy gap in solution and solid phases - Schaberle, Fábio António (2020)
The process of singlet-exciton fission (SEF) has attracted much attention of late. One of the most popular SEF compounds is TIPS-pentacene (TIPS-P, where TIPS = triisopropylsilylethynyl) but, despite its extensive use as both a reference and building block, its photophysical properties are not so well established. In particular, the triplet state excitation energy remains uncertain. Here, we report quantitative data and spectral characterization for excited-singlet and -triplet states in dilute solution. The triplet energy is determined to be 7940 1200 cm1 on the basis of sensitization studies using time-resolved photoacoustic calorimetry. The triplet quantum yield at the limit of low concentration and low laser intensity is only ca. 1%. Self-quenching occurs at a high solute concentration where the fluorescence yield and lifetime decrease markedly relative to dilute solution but we were unable to detect excimer emission by steady-state spectroscopy. Short-lived fluorescence, free from excimer emission or phosphorescence, occurs for crystals of TIPS-P, most likely from amorphous domains.